Reprogramming astroglia into neurons with hallmarks of fast-spiking parvalbumin-positive interneurons by phospho-site-deficient Ascl1 - Marichal, Nicolás; Péron, Sophie; Beltrán Arranz, Ana; Galante, Chiara; Franco Scarante, Franciele; Wiffen, Rebecca; Schuurmans, Carol; Karow, Marisa; Gascón, Sergio; Berninger, Benedikt (Science Advances, 2024)
Cellular reprogramming of mammalian glia to an induced neuronal fate holds the potential for restoring diseased brain circuits. While the proneural factor achaete-scute complex-like 1 (Ascl1) is widely used for neuronal reprogramming, in the early postnatal mouse cortex, Ascl1 fails to induce the glia-to-neuron conversion, instead promoting the proliferation of oligodendrocyte progenitor cells (OPC). Since Ascl1 activity is posttranslationally regulated, here, we investigated the consequences of mutating six serine phospho-acceptor sites to alanine (Ascl1SA6) on lineage reprogramming in vivo. Ascl1SA6 exhibited increased neurogenic activity in the glia of the early postnatal mouse cortex, an effect enhanced by coexpression of B cell lymphoma 2 (Bcl2). Genetic fate-mapping revealed that most induced neurons originated from astrocytes, while only a few derived from OPCs. Many Ascl1SA6/Bcl2-induced neurons expressed parvalbumin and were capable of high-frequency action potential firing. Our study demonstrates the authentic conversion of astroglia into neurons featuring subclass hallmarks of cortical interneurons, advancing our scope of engineering neuronal fates in the brain.
CRIS-Team Scopus Importer:2024-11-08